2019
DOI: 10.1186/s43088-019-0002-3
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal removal using a fixed bed bioreactor packed with a solid supporter

Abstract: Background: Different bacterial isolates were obtained from a much-polluted lake (Lake Mariout) in Alexandria, Egypt. They were tested to bio-remove different heavy metal ions (Cu 2+ , Pb 2+ , Cd 2+ , Co 2+ , Ni 2+ , Zn 2+ , Mn 2+ , and Fe 3+ ). In addition, this study was aimed to create a fixed bed column to enhance the metal removal from some polluted wastewater samples. Results: The potent bacterium was selected and identified as Pseudomonas aeruginosa using the 16SrRNA gene sequence. The effect of some ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To reduce the environmental effect of synthetic dyes, a range of strategies for removing them from water and wastewater have been developed. The technologies include chemical precipitation, chemical oxidation, adsorption, decolorization by photocatalysis and/or oxidation processes [20,21], microbiological or enzymatic degradation, and so on [24,25].…”
Section: Synthetic Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the environmental effect of synthetic dyes, a range of strategies for removing them from water and wastewater have been developed. The technologies include chemical precipitation, chemical oxidation, adsorption, decolorization by photocatalysis and/or oxidation processes [20,21], microbiological or enzymatic degradation, and so on [24,25].…”
Section: Synthetic Dyesmentioning
confidence: 99%
“…Pseudomonas aeruginosa was isolated from Mariout Lake in Alexandria, Egypt, and used to remove Cd 2+ , Fe 3+ , Cu 2+ , Mn 2+ , Co 2+ , Zn 2+ , Ni 2+ , and Pb 2+ [24]. They fabricated a fixed bed glass bioreactor packed with a solid support luffa bulb and observed the removal of metal ions in the wastewater samples.…”
Section: Bioreactors In Metal Removalmentioning
confidence: 99%
“…About 80% for Cu(II), 98% for Pb(II), 50% for Ni(II) and 77% for Zn(II) bioremediation was found to be achieved in a Membrane bioreactor (MBR) system (Katsou et al, 2011). It was found that the fixed bed bioreactors was able to increase the efficiency towards the removal of metals (Cu 2+ , Pb 2+ , Cd 2+ , Co 2+ , Ni 2+ , Zn 2+ , Mn 2+ , and Fe 3+ ) in polluted environmental samples by a strain of Pseudomonas aeruginosa to control many harmful health hazard substances (Ibrahim et al, 2019). On the other hand, removal of heavy metals including nickel, arsenic, cadmium, antimony and lead by membrane bioreactor was investigated by Komesli (2014).…”
Section: Bioreactormentioning
confidence: 99%
“…The biogeochemical cycle that occurs in the marine environment with the diversity of existing ecosystems causes the ocean to have a natural ability to maintain its balance, including detoxifying the toxic nature of toxic components that enter marine waters [8], [9]. Thus, the quality of marine biological wealth can be massively maintained and will continue to support the sustainability of human life [10].…”
Section: Introductionmentioning
confidence: 99%